2016
DOI: 10.1158/1078-0432.ccr-15-2535
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of FoxM1-Mediated DNA Repair by Imipramine Blue Suppresses Breast Cancer Growth and Metastasis

Abstract: Purpose The approaches aimed at inhibiting the ability of cancer cells to repair DNA strand breaks have emerged as promising targets for treating cancers. Here, we assessed the potential of imipramine blue (IB), a novel analogue of anti-depressant imipramine, to suppress breast cancer growth and metastasis by inhibiting the ability of breast cancer cells to repair DNA strand breaks by homologous recombination. Experimental Design The effect of IB on breast cancer growth and metastasis was assessed in vitro a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…As a member of an evolutionarily conserved family of transcription factors characterized by a DNA-binding domain called the Forkhead Box (Kalin et al, 2011), FOXM1 is also known as a representative proliferationassociated transcription factor, such as prostate cancer (Lokody, 2014), hepatocellular carcinoma (Yamashita et al, 2014), glioblastoma (Gong et al, 2015), and bladder cancer (Kim et al, 2014). The overexpression of FOXM1 observed that FOXM1 is associated with an aggressive phenotype and poor prognosis in patients with breast cancer (Rajamanickam et al, 2016). Furthermore, Balli et al (2013) reported that FOXM1 could promote the epithelialmesenchymal transition (EMT) of lung cancer cells through stimulating the transcription of Slug.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of an evolutionarily conserved family of transcription factors characterized by a DNA-binding domain called the Forkhead Box (Kalin et al, 2011), FOXM1 is also known as a representative proliferationassociated transcription factor, such as prostate cancer (Lokody, 2014), hepatocellular carcinoma (Yamashita et al, 2014), glioblastoma (Gong et al, 2015), and bladder cancer (Kim et al, 2014). The overexpression of FOXM1 observed that FOXM1 is associated with an aggressive phenotype and poor prognosis in patients with breast cancer (Rajamanickam et al, 2016). Furthermore, Balli et al (2013) reported that FOXM1 could promote the epithelialmesenchymal transition (EMT) of lung cancer cells through stimulating the transcription of Slug.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve better outcomes in breast carcinoma, DNA repair protein inhibition strategies are highly necessary. In the same direction, imipramine blue, which is an inhibitor of forkhead box protein M1 (FOXM1)-mediated HR DNA repair pathways, inhibits breast cancer growth 42. Ataxia telangiectasia and Rad3-related kinase, a member of the phosphatidylinositol-3-related protein kinases, is the basis for strategies to silence several types of cancer because these kinases are responsible for the DNA damage response during chemotherapy and radiation therapy in cancer patients 43.…”
Section: Small Molecule Inhibition and Homologous Recombinationmentioning
confidence: 99%
“…Apart from this, imipramine compound has also shown a better result for the treatment of patients with spontaneous panic attack as compared to placebo [30]. Recently, Imipramine blue, a unique analogue of imipramine, an anti-depressant drug, has shown its role in suppression of breast cancer and metastasis by inhibiting the homologous recombination mediated DNA repair mechanism of breast cancer cells [31]. The severity of visceral leishmaniasis in endemic zone of Indian subcontinent and lack of efficacious drug urge an urgent requirement of an antileishmanial drug with good efficacy and minimum toxicity.…”
Section: Discussionmentioning
confidence: 99%